2005
DOI: 10.1108/14691930510592799
|View full text |Cite
|
Sign up to set email alerts
|

The role of social capital in the relationship between human capital and career mobility

Abstract: PurposeThis study aims to examine what kind of role social capital plays in the relationship between human capital and career outcomes, with a particular focus on testing the mediation and moderation models.Design/methodology/approachUsing data compiled from 111 employees at three financial institutions in Taiwan, social capital was measured by employees based on network in‐degree centrality, and development potential was measured by supervisors.FindingsResults showed that the effects of human capital on devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 44 publications
4
70
0
1
Order By: Relevance
“…In addition, considering the nature of the entrepreneurial projects proposed in phase 2, international students will have the opportunity to gain invaluable inter-cultural knowledge and understanding (from working within multi-cultural teams) and to proactively engage in their local communities. We believe that by helping international students -build capacity within‖, and by enhancing their prospects of acquiring social capital (Lin & Huang, 2005), this program will significantly contribute to their effective integration and retention in their host communities. Future research may examine the level of impact of our training program on self-discovery and on each of the three self-regulation competencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, considering the nature of the entrepreneurial projects proposed in phase 2, international students will have the opportunity to gain invaluable inter-cultural knowledge and understanding (from working within multi-cultural teams) and to proactively engage in their local communities. We believe that by helping international students -build capacity within‖, and by enhancing their prospects of acquiring social capital (Lin & Huang, 2005), this program will significantly contribute to their effective integration and retention in their host communities. Future research may examine the level of impact of our training program on self-discovery and on each of the three self-regulation competencies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the authors of this paper believe that effective social integration is critical for enhancing the prospects of international student retention, after their graduation. The acquisition of human capital (i.e., knowledge and skills) through education and work experience is strengthened by the acquisition of social capital (i.e., networks of social relationships) (Lin & Huang, 2005;Szelenyi, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lin and Huang (2005) assert that employees who are highly educated have had more chances to be promoted, and so they are more likely to attend career management oriented activities. In this direction, we believe of prevalent of certain association between HR factors and human capital variables.…”
Section: Human Resource Management and Human Capitalmentioning
confidence: 99%
“…The role of social capital as a mediator has been approved by different studies (16). For example, a study in Taiwan has shown its role in the relationship between human capital and career mobility (17); also, some researchers emphasized on positive impact of social capital on self-control and on mental and social performance (18). To the best of our knowledge, no study showed a cumulative effect of social capital and organization commitment on job stress and also there is no study to examine the mediator role of social capital variable on the relation between organization commitment and job stress variables.…”
Section: Introductionmentioning
confidence: 99%